2022
DOI: 10.1371/journal.pone.0255715
|View full text |Cite
|
Sign up to set email alerts
|

The orphan drug dichloroacetate reduces amyloid beta-peptide production whilst promoting non-amyloidogenic proteolysis of the amyloid precursor protein

Abstract: The amyloid cascade hypothesis proposes that excessive accumulation of amyloid beta-peptides is the initiating event in Alzheimer’s disease. These neurotoxic peptides are generated from the amyloid precursor protein via sequential cleavage by β- and γ-secretases in the ’amyloidogenic’ proteolytic pathway. Alternatively, the amyloid precursor protein can be processed via the ’non-amyloidogenic’ pathway which, through the action of the α-secretase a disintegrin and metalloproteinase (ADAM) 10, both precludes amy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“… 126 Parkin et al found in SH-SY5Y cells that DCA (10 and 20 mmol/L) increased the level of sAPPα and decreased the levels of sAPPβ and Aβ but did not change the activity and mRNA expression of ADAM10 and BACE1, which proved that DCA could reduce the generation of Aβ. 50 However, since the effect of DCA on the protein expression level of BACE1 was not measured, the mechanism by which DCA affects the generation of Aβ remains to be explored. Velliquette et al found that using drugs (insulin, 2-deoxyglucose, 3-nitropropionic acid, and kainic acid) to inhibit energy metabolism in APP transgenic mice increased BACE1, sAPPβ, and Aβ40 levels, suggesting that reduced energy metabolism increases Aβ production by increasing BACE1 expression levels.…”
Section: Neuroprotective Effects and Mechanisms Of Dichloroacetatementioning
confidence: 99%
“… 126 Parkin et al found in SH-SY5Y cells that DCA (10 and 20 mmol/L) increased the level of sAPPα and decreased the levels of sAPPβ and Aβ but did not change the activity and mRNA expression of ADAM10 and BACE1, which proved that DCA could reduce the generation of Aβ. 50 However, since the effect of DCA on the protein expression level of BACE1 was not measured, the mechanism by which DCA affects the generation of Aβ remains to be explored. Velliquette et al found that using drugs (insulin, 2-deoxyglucose, 3-nitropropionic acid, and kainic acid) to inhibit energy metabolism in APP transgenic mice increased BACE1, sAPPβ, and Aβ40 levels, suggesting that reduced energy metabolism increases Aβ production by increasing BACE1 expression levels.…”
Section: Neuroprotective Effects and Mechanisms Of Dichloroacetatementioning
confidence: 99%